MAKNA VERBA ANGNGERANG 'MEMBAWA' DALAM BAHASA KONJO DIALEK KONJO PESISIR: KAJIAN METABAHASA SEMANTIK ALAMI - Normawati Normawati (Kantor Bahasa Provinsi Maluku Utara, 2020)
This study is to explain the meaning of verb angngerang ‘membawa’ in coastal Konjo dialect of Konjo language by using Natural Semantic Metalanguage (NSM) theory. This study uses qualitative method. This study is conducted by three stages, such as: (1) data collecting, (2) data processing, and (3) presentation of results from data processing. The data contains the verb of angngerang ‘membawa’ from native speakers of coastal Konjo dialect of Konjo language. By applying the interview and stimulation technique is reached that verb angngerang ‘membawa’ is included in action verb category. Data is recorded in the card data and presented by using explication technique or paraphrasing. The result of analysis showed that the verb angngerang‘membawa’ consist of (1) verb, (2) 14 lexicons, and (3) the entire lexicons are NSM syntactic patterned: X doing something to Y and Y moving.